Pemberdayaan Kelompok Tani Lokakarya Dalam Pemanfaatan Kain Perca Desa Lembah Sari Kecamatan Rumbai Pesisir - Wiyati, Rita; Maryanti, Sri; Thamrin, M (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2019)
Lembah Sari Village, Rumbai Pesisir Subdistrict, there are a number of farmer groups from one of the Workshop farmer groups, some of the farmer groups available are inactive. During the survey meeting with the chairman of GAPOKTAN, he stated that his members wanted to be re-empowered in other words, the Workshop group was reactivated in the activities of its farmer groups. Most of the members are pure housewives who only take care of the family, without any desire and willingness to seek additional hope. Based on this, our community service team from the faculty of economics gathered provided the skills and empowered the mothers of the LokaKarya farmer group in Lembah Sari village in their skills in making women's accessories. The purpose of this Community Service is to produce products in the form of bross, necklaces or bracelets for women's accessories that can help increase family money and to motivate mothers of members of the Lembah Sari village farmer group to become entrepreneurs by producing their products. The specific target that wants to succeed is so that the members of the farmer group are more creative and innovative to have a business with cheap capital. The method used to achieve the intended purpose is to conduct counseling about the interests of entrepreneurship and training in making bross hijab and also not using large capital considering the members of the farmer group workshops have less established investments. The methods of implementing the program that will be carried out are: understanding in entrepreneurship, training in making headscarf accessories, assistance in making headscarf accessories. All of these methods are an integral part of this IbM program. The results and results obtained in this PKM, when the pretest of the majority of PKM participants were still wrong, the participants were less likely to postpone the pretest, because some members of the farmer group had received training, some were active in the village PKK, and thus increased the number of participants who did not need the spirit of the members present. And in the simulation the participants quickly understood it and were creative. The essence of this service requires motivating members of the farmer group to be able to be enthusiastic about entrepreneurship, no matter how small the effort that we do, still must be with perseverance and sincerity.